KONSEP PERADILAN SENGKETA PEMILIHAN KEPALA DAERAH - Andi Arfan Sahabuddin (Fakultas Hukum Univesitas Kristen Indonesia Paulus, 2020)
In the Decision of the Constitutional Court of the Republic of Indonesia Number 97/PUU/2013, it is stated that the handling of The Regional Election disputes is no longer be the authority of the Constitutional Court. This raises a consequences, the Regional Election disputes wil be handled through the Special Judiciary. This study aims to analyze the concept of Regional Election disputes court. This study uses a normative method with statute approach. The result of this study shows that the formation of a Special Judiciary to handle the Regional Election disputes is a necessity because it is a mandate of the Law. In order for the handling of Regional Election disputes can be effective, the Special Judiciary should be under the State Administrative Court.